The neural basis of nonword repetition in children with developmental speech or language disorder: An fMRI study. (17th February 2020) - Pigdon, Lauren; Willmott, Catherine; Reilly, Sheena; Conti-Ramsden, Gina; Liegeois, Frederique; Connelly, Alan; Morgan, Angela T.
Abstract: Developmental language disorder (DLD) and developmental speech disorder (DSD) are highly prevalent childhood conditions. An impaired ability to repeat nonsense words ("nonword repetition"), is claimed to be a robust behavioural marker for these conditions. Yet how brain function is altered during this task remains poorly understood. Previous research suggests that DLD or DSD may be associated with reduced brain activation in the inferior frontal and posterior temporal regions when compared to controls. However, this research is limited by within and between group variability in age, speech/language phenotype, and comorbidities. Here, we used functional MRI to examine brain activation during nonword repetition. As anticipated, behavioural findings confirmed that the DLD and DSD groups had poorer nonword repetition performance compared to typical controls. In contrast, fMRI revealed no statistically significant differences in brain activation, despite the groups appearing to engage slightly different regions when compared at identical thresholds. Therefore, whilst nonword repetition is a sensitive clinical marker for DLD and DSD, the findings from this study suggest that this task is not a sensitive brain MRI marker for children with these disorders, unlike for individuals with single gene mutations like FOXP2 mutations. Highlights: Nonword repetition a sensitive clinical marker for DLD and DSD. No significant differences in nonword repetition fMRI for DLD, DSD and controls. Nonword repetition not a sensitive brain MRI marker for children with DLD or DSD.